2020
DOI: 10.1542/peds.2019-2057
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Associated Urinary Tract Infection Reduction in a Pediatric Safety Engagement Network

Abstract: BACKGROUND: Catheter-associated urinary tract infections (CAUTIs) are a leading cause of health care-associated infection. Catheter insertion bundles (IBs) and maintenance bundles (MBs) have been developed to prevent CAUTIs but have not been extensively validated for use in pediatric populations. We report the CAUTI prevention efforts of a large network of children's hospitals.METHODS: Children's hospitals joined the Children's Hospitals' Solutions for Patient Safety engagement network from 2011 to 2017, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…These interventions revealed a decrease and then eradication of CAUTI. As well as (25) who concluded that, after the implementation of the pediatric CAUTI insertion and maintenance bundles care, CAUTI rates reduced among hospitalized children with indwelling urinary catheters after intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions revealed a decrease and then eradication of CAUTI. As well as (25) who concluded that, after the implementation of the pediatric CAUTI insertion and maintenance bundles care, CAUTI rates reduced among hospitalized children with indwelling urinary catheters after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects associated with indwelling urinary catheters include increases in length of hospital stay (LOS), health care costs, morbidity and mortality in hospitalized pediatric patients. (25,26) The National Healthcare Safety Network revealed that pooled mean CAUTI rates were similar in children and adults, the national pooled mean for pediatric intensive care units (PICUs) was 2.5 infections per 1000 catheter-days.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The burden of CAUTI in pediatric patients is not well defined; however, bundles adapted from work in adults have been applied to the pediatric population with favorable results. 5 Urinary catheters remain one of the most common medical devices experienced by adults in emergency departments and hospitals worldwide. Often, these devices are placed and maintained in use without an appropriate clinical indication to justify the risk compared to the benefit.…”
Section: Section 1: Rationale and Statements Of Concernmentioning
confidence: 99%
“…Solutions for Patient Safety, an engagement network of >145 North American children's hospitals, has used this concept of 'All Teach, All Learn' to reduce harm to hospitalized children, including HAIs like catheter-associated bloodstream infections (CLABSIs), surgical site infections (SSIs), and catheter-associated urinary tract infections (CAUTIs). [9][10][11] Shared learning includes both successes and failures. A key tenet of improvement science is that failing is inevitable and acceptable and can lead to insights that contribute to success.…”
Section: Improvement Science As a Disciplinementioning
confidence: 99%
“…10,48,64,65 For example, the Solutions for Patient Safety collaborative has reduced CLABSIs (13.7%), CAUTIs (56.6%) and SSIs (16.6%) since 2012. 11,66 Another multicenter collaborative of 5 adult hospitals in Brazil reduced CLABSI, CAUTIs and VAPs. 51 Regular communication and collaboration among collaborative members has been cited as a key factor for their success.…”
Section: Multicenter Collaborativesmentioning
confidence: 99%